WAYS TO OPTIMIZE THE RESTORATION OF ADJOINING SURFACES OF LATERAL TEETH - Іваницький, І.О. (World of Medicine and Biology, 2016)
Caries of permanent lateral teeth is the most common reason for patients’ reference to the dentist. At the same time, filling carious cavities on approximal surfaces in case of preserved adjacent teeth, even using the modern restoration technology, remains a rather challenging problem up to the present. Incorrect restoration of coronal tooth leads to complications such as chipped tooth wall, fallen out fillings, development of increased sensitivity, secondary caries, pulpitis, periodontitis, inflammation and injury of interdental papilla. Recent studies indicate a sufficiently large number of low-quality dental restorations. Researchers assert that the problem of creating a tight anatomical contact between the adjacent lateral teeth, as well as providing the high-quality polymerization of filling material on approximal wall still remains not completely settled for modern dentistry.The aim of the research is to develop a more efficient technology for restoration of adjoining surfaces of lateral teeth.Materials and methods. We observed 73 patients, affected by caries on approximal surfaces of 97 first and second molars in the maxilla and mandible.Research results. We provided a method to improve the techniques for creation of a contact point in the restoration of lateral teeth, the essence of which is to restore the exterior walls of the cavity with liquid composite followed by filling the central cavity with conventional composite materials or with those of high density (Application number u 201600034 as of 04.01.2016).Before the restoration, one must necessarily conduct the professional cleaning of teeth, then under adequate anaesthesia, the dissection of cavity (cavities) or removal of restorations that do not meet the requirements is performed. After isolation of the working field with cofferdam, the contour matrix is set which adapts to the cervical area using a wooden wedge administered from the oral or vestibular side of interdental space, depending on the density and preservation of the walls. This done, enamel and dentin are treated with acid and rinsed with water current. After complete drying, the adhesive preparation of the cavity is carried out. The next step is applying 1 mm of the liquid composite to entire height of the inner surface of matrix, followed by activation of matrix to the side of the tooth and polymerization of the filling material. Subsequently, the cavity is filled by means of traditional techniques of layered embedding and polymerization of composite material of normal or high density.After removal of sectional matrix using forceps, and withdrawal of cofferdam, the additional polymerization is carried out, culminating in the final modelling of occlusal surface and correction of restoration. At the final stage, grinding and polishing with restoration discs, polishing cups and heads of different abrasiveness are conducted, whereupon the finishing lighting is to be held.As a result of re-examination after 6 and 12 months, it can be concluded that restoration carried out using the proposed method met all functional and aesthetic requirements and did not need corrections.
Keywords: restoration; lateral teeth; adjoining surface; the contact point